Study on the approach to scoliosis in children of age prepuberty - Mihai Constantinescu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
This paper aims to present some of the usual aspects that accompany the processes of installation and development of scoliotic attitudes in prepubertal children. The aspects presented are known and are not new, however the approach to postural deficits at this age is superficial in terms of investigations/assessments. Often discovered too late, many spinal deviations are progressive and difficult to manage. For these reasons, we believe that this paper can raise the attention of specialists and not only a wake-up call to combat these postural deficits that may start in prepubertal age.